2022
DOI: 10.3892/etm.2022.11201
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and lung injury in rats following acute diquat exposure

Abstract: Diquat (1,1'-ethylene-2,2'-bipyridylium) is a type of widely used agricultural chemical, whose toxicity results in damage to numerous tissues, including the lung, liver, kidney and brain. The aim of the present study was to establish a rat model of acute diquat exposure and explore the relationship between diquat concentration, and kidney and lung injury, in order to provide an experimental basis for clinical treatment. A total of 140 healthy adult male Wistar rats were randomly divided into control and exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this case report, diquat concentration in the blood was reduced via hemoperfusion and hemofiltration. Previous studies reported a higher concentration of diquat in the liver, brain, kidney, and skeletal muscles than in the blood in the early stages of poisoning (1,11,16). Thus, we hypothesized that hemoperfusion and hemofiltration eliminate poisons in tissues at a lower rate than that in blood.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this case report, diquat concentration in the blood was reduced via hemoperfusion and hemofiltration. Previous studies reported a higher concentration of diquat in the liver, brain, kidney, and skeletal muscles than in the blood in the early stages of poisoning (1,11,16). Thus, we hypothesized that hemoperfusion and hemofiltration eliminate poisons in tissues at a lower rate than that in blood.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with severe cases may develop acute kidney injury, as noted in the present cases, as diquat accumulates in high concentrations in the kidneys ( 1 ). Animal studies demonstrate that diquat can easily cause edema, degeneration, and necrosis of the renal tubules ( 11 ). Major pathological changes observed on autopsy include congested kidneys, necrotic renal tubules, and intact glomeruli ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Scr is an important response index of acute renal failure (29). As a risk factor for QD poisoning, the trend of Scr deterioration in DQ poisoning death group was significantly higher than that in survival group, and had a significant negative correlation with survival time, suggesting that Scr could reflect the severity and prognosis of DQ poisoning (30).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike paraquat, diquat seldom causes pulmonary fibrosis, at least during a short period or at the early stage. In one study, it only caused infiltration of inflammatory cells, resulting in a diffuse exudative change in both lung fields [ 8 ]. However, differential diagnosis or underdiagnosis might lead to inefficient therapy, which might cause the patient to develop pulmonary fibrosis and result in respiratory failure, causing death.…”
mentioning
confidence: 99%